2019
DOI: 10.1002/mgg3.757
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Long non‐coding RNA NORAD promotes the occurrence and development of non‐small cell lung cancer by adsorbing MiR‐656‐3p

Abstract: Background To explore the role of non‐coding RNA activated by DNA damage (NORAD), a long non‐coding ribonucleic acid (lncRNA), in non‐small cell lung cancer (NSCLC) and its possible mechanism. Methods Quantitative real‐time polymerase chain reaction was adopted for the detection of the expression levels of NORAD, micro RNA (miR)‐656‐3p, and AKT serine/threonine kinase 1 (AKT1). The effects of NORAD, miR‐656‐3p, and AKT1 on cell proliferation and migration were examined through the Cell Counting Kit‐8 (CCK‐8) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…LncRNAs function as guides, scaffolds, and molecular sponges in their interactions with proteins, microRNAs (miRNAs), and mRNAs, thereby creating complex networks that regulate various physiological and pathological processes, including cancer initiation and progression [8]. Recently, several studies revealed the contribution of lncRNAs to the formation and progression of multiple types of cancers, including NSCLC [9][10][11]. A large number of lncRNAs are expressed abnormally in NSCLC, e.g., HOXA-AS2 [12], LEF1-AS1 [13], and BLACAT1 [14].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs function as guides, scaffolds, and molecular sponges in their interactions with proteins, microRNAs (miRNAs), and mRNAs, thereby creating complex networks that regulate various physiological and pathological processes, including cancer initiation and progression [8]. Recently, several studies revealed the contribution of lncRNAs to the formation and progression of multiple types of cancers, including NSCLC [9][10][11]. A large number of lncRNAs are expressed abnormally in NSCLC, e.g., HOXA-AS2 [12], LEF1-AS1 [13], and BLACAT1 [14].…”
Section: Introductionmentioning
confidence: 99%
“…The role of lncRNA NORAD in NSCLC was discovered by Chen et al . in promoting the development of lung cancer . However, the role of lncRNA SNHG14 in lung cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…15 A novel miRNA miR-656-3p has been regarded as a tumor suppressor in glioma and NSCLC. 16,17 However, little is known about the role of this miRNA in CDDP resistance in NSCLC. Sex-determining region Y-related highmobility group box (SOX) family has key roles in tumorigenesis and metastasis of human cancers.…”
Section: Introductionmentioning
confidence: 99%